Influence of Fracture Stability on Early Patient Mortality and Reoperation After Pertrochanteric and Intertrochanteric Hip Fractures. Issue 12 (December 2015) - Chehade, Mellick J.; Carbone, Tania; Awward, Danny; Taylor, Anita; Wildenauer, Corinna; Ramasamy, Boopalan; McGee, Margaret
Abstract : Objectives: To determine the influence of fracture stability on early patient mortality and complications requiring reoperation after trochanteric hip fracture. Design: Prospective consecutive cohort study. Setting: The orthopaedic unit of a public teaching hospital. Participants: Seven hundred twenty-eight patients with 743 consecutive stable (n = 446) pertrochanteric and unstable (n = 297) pertrochanteric or intertrochanteric fractures (median age: 84 years, 71% females) resulting from a low-impact injury and surgically managed. Mean follow-up of surviving patients was 4 years (range: 2–6 years). Intervention: Fracture fixation by dynamic hip screw extramedullary device or intramedullary nail (Austofix or Gamma3) based on surgeon preference. Main Outcome Measures: Mortality within 6 and 12 months and surgical complications requiring device reoperation within 12 months of surgery (multivariate logistic regression and Kaplan–Meier survival analyses). Results: Patients with unstable fractures were at 1.61 times (95% confidence interval: 1.18–2.21, P = 0.003) and 1.37 times (95% confidence interval: 1.02–1.83, P = 0.037) greater odds of dying within 6 and 12 months, respectively, than those with stable fractures. Older age, male gender, higher American Society of Anesthesiologists classification, in residential care, and inpatient-reported medical complications were also independent risk factors for early mortality. Increasing fracture instability and fixation using the Austofix nail were associated with early device reoperation. Comparable results were reported for the dynamic hip screw and Gamma3 nail, although the Gamma3 nail may offer advantages for more complex unstable fractures. Conclusions: Fracture instability influences early mortality after surgical fixation of trochanteric hip fracture. The Austofix double lag screw device had suboptimal results. Level of Evidence: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.